A educação a distância como possibilidade de qualificação dos recuperandos do sistema prisional: um estudo de caso - Santos, Thais Teixeira (2018)
This research proposal aims to identify contributions of the EaD in the process of resocialization of people who are distressed in the prison system. The crisis in the Brazilian prison system and the violation of prisoners' rights is a situation that extends throughout Brazil. Overcrowding aggravates the precariousness of penitentiaries and contributes to internal violence, the system has not been able to reach its goal, which is to recover and reintegrate the prisoner into society as a function of punishment. One of the alternatives for reversing the current framework of conventional criminal execution, the APAC has the philosophy of recovering the prisoner, protecting society, helping victims and promoting justice. In APAC, the prisoner has access to the study, and distance education can be a relevant strategy for these victims. The proposal will have a qualitative approach with the accomplishment of a case study with the recoverees that carry out the superior course within the APAC. It is intended that this research be carried out within 18 months. It is hoped to identify how the EAD is contributing to the study access and, consequently, to the prisoners' recovery.